Multifunctional Few-Layer MoS2 for Photodetection and Surface-Enhanced Raman Spectroscopy Application with Ultrasensitive and Repeatable Detectability - Majee B.P.; Mishra S.; Pandey R.K.; Prakash R.; Mishra A.K. (My University, 2025)
Molybdenum disulfide (MoS2) with unique electronic and physical properties has attracted great interest in the field of next-generation optoelectronic and photonic devices for societal benefits. In view of considering the great challenge in scaling the monolayer MoS2, the current focus is on improving the performance of few-layer MoS2-based optoelectronic and photonic devices. Here, we report multifunctional large area-grown few-layer MoS2 for the photoresponse and detection of organic pollutants. The few-layer MoS2 (thickness of around 4 nm) has been successfully synthesized over highly doped p-type Si via the chemical vapor deposition technique, and their optical properties have been studied using Raman and photoluminescence spectroscopy. Here, we report the photoresponse of a pristine few-layer MoS2/Si heterojunction under low-power white light illumination (0.15 mW cm-2) with 0.1413 A W-1 photoresponsivity at -2 V. This photoresponsivity is the best to our knowledge under white light illumination condition concerning light intensity. Further, few-layer MoS2 over Si has been successfully demonstrated as a surface-enhanced Raman spectroscopy (SERS) substrate for the ultrasensitive detection of Rhodamine 6G (R6G) at nanomolar concentration, which is the highest detection limit for R6G using pristine MoS2 to the best of our knowledge. Additionally, we also examined the treatment of adsorbed R6G over few-layer MoS2 in the presence of water under visible light illumination for reusability of the SERS substrate with repeated detectability. © 2019 American Chemical Society.